Burnout among Medical Assistants at Shahid Sadoughi University of Medical Sciences - Amirhossein Rahavian; Mehdi Abedinzadeh; Seyed Masoud Hoseini; Omid Aminirad; Tahereh Shafaghat; Danial Dehghani Firouzabadi (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Shahīd Ṣadūqī Yazd)
Introduction: Professional burnout is a state of mental exhaustion and it is a passive reaction caused by chronic occupational stress that is not properly managed. Physician burnout is more prevalent than in the general population, particularly among residents. The aim of this study is to investigate burnout among the residents of Shahid Sadoughi University of Medical Sciences in Yazd. Methods: This analytical cross-sectional study was conducted on 214 residents of Shahid Sadoughi University of Medical Sciences, Yazd, in 2022-2023 based on the Maslach Burnout Questionnaire. Residents were categorized into no, moderate and severe burnout groups using rates of 33% and 66%. Residents’ career choices, including their decision to enter the medical field and choose a specialty, as well as their priorities were also surveyed. Results: A total of 151 residents participated in this study (70.5%) with the mean age of 31.91±5.02 years. The mean burnout score was 51.25±26.97. Professional burnout did not differ significantly by gender, marital status, having children, type of specialty (surgical or non-surgical), or residency level. Burnout was highest in pediatrics, orthopedics and cardiology, and lowest in emergency medicine, infectious diseases and ophthalmology. This difference was significant between the disciplines (P-value=0.003). The most important unmet needs cited by residents were a suitable fellowship (77.5%) and fewer working hours (76.8%). 63 residents regretted their choice of medicine (41.7%) and 38 (25.2%) regretted their choice of specialty. There was no significant association between age and professional burnout (P-value=0.057). Conclusion: More than half of the residents suffer from moderate professional burnout. It is recommended to improve the conditions for residents, to conduct more studies with details and to evaluate this topic regularly.